1989
DOI: 10.1111/j.1439-0531.1989.tb00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Vitrified Sheep Morula

Abstract: Contents The aim of the experiment was to determine the susceptibility to vitrification of the sheep morula. As a vitrification medium the mixture of 35% glycerol + 30% 1,2 propanediol or 30% glycerol + 35% 1,2 propanediol was used. The embryos were fiozen in glass ampules placed for 5 min in nitrogen uapour before plunging to liquid nitrogen. Dilution after rapid thawing was done in one step in a 1M sucrose solution. The pregnancies were obtained only when the embryos were transferred immediately after thawin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
6
0
3
Order By: Relevance
“…First Willadsen et al (1976), then Moor and Bilton (1977) and finally Smorąg et al (1977) obtained live lambs following transfer of sheep morulae and blastocysts. The first successful vitrification of ovine embryos was carried out by Gajda et al (1989). We demonstrated that the survival of transferred vitrified sheep morulae (60%) is comparable to that obtained after transfer of embryos frozen using the conventional slow method.…”
Section: Speciesmentioning
confidence: 66%
“…First Willadsen et al (1976), then Moor and Bilton (1977) and finally Smorąg et al (1977) obtained live lambs following transfer of sheep morulae and blastocysts. The first successful vitrification of ovine embryos was carried out by Gajda et al (1989). We demonstrated that the survival of transferred vitrified sheep morulae (60%) is comparable to that obtained after transfer of embryos frozen using the conventional slow method.…”
Section: Speciesmentioning
confidence: 66%
“…This may be explained because pig oocytes and embryos are characterized by a high lipid content, which is stored as droplets in the cytoplasm [38,41]. This high lipid content has a negative influence on successful manipulations of oocytes and embryos, thereby resulting in cryopreservation methods with less success for pig than in bovine [19]. This is supported on the low rates of ED reported by Nagashima et al [36] and Wu et al [52] or blastocyst formation reported by Somfai et al [45].…”
Section: Discussionmentioning
confidence: 99%
“…-La viabilidad observada en los ovocitos inmaduros de porcino y ovino con el proceso de vitrificación ha generado información que parece indicar que los ovocitos de porcino resisten menos al proceso de vitrificación debido al alto contenido de lípidos en su citoplasma (Gajda, 2009). Por consiguiente, se considera que los ovocitos de ovino tendrán un mayor porcentaje de viabilidad, maduración y desarrollo embrionario después de la vitrificación con respecto a los ovocitos porcinos sometidos a las mismas condiciones de criopreservación.…”
Section: Hipótesis Particularesunclassified
See 2 more Smart Citations